KONSTRUKSI TES GAYA BELAJAR BERDASARKAN TEORI BELAJAR EKSPERIENSIAL DAVID A. KOLB - Pratiwi, Ari (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
The Construction of Learning Style Tests based on the Theory of Experiential Learning Style of David A. Koelb. This study aimed to examine the construction of student learning styles test based on Experiential Learning theory of David A. Koelb (1971). There are 4 elements involved in the experiential learning cycle, namely concrete experience (CE), Reflective Observation (RO), Abstract Conceptualization (AC) and Active Experimentation (AE). Based on the four elements, the research paired 86 items (forced-choice pair) and tested a sample of 350 students. Sample was taken proportionately from five programs of study/majors (Psychology, Sociology, Communication, Political Science, and International Relations) at the University of Brawijaya. Analysis of the reliability coefficient on the item produced (Alpha Cronbach) is relatively high, CE= 0.448; RO = 0.551; AC= 0.450, and AE = 0.409. The item analysis results obtained by psychometric characteristics test (correlation between each item with total item, item reliability index and the item discrimination) are also relatively high, with Chi square at 2.138 with a significance number 0.544. These results indicate that FISIP students of Brawijaya University do not have a specific learning style tendency. Basically, they significantly posses equal learning style.Key Words : Tests Construction, Learning Style